Cultural and historical origins of modern sports (the first message) - Сутула, Василь (Slobozhanskyi Herald of Science and Sport, 2017)
Vasyl Sutula Purpose: to reveal the cultural and historical origins of modern sports. Material & Methods: research methods consist of the analysis of the specialized literature that highlights various aspects of the development of the field of people’s activities related to the use of physical exercises, as well as the application of a systematic and historiographical approach to the analysis of this problem. To solve the tasks set, an analysis was carried out of the print publications available in the Google Books library, which cover the period from the late 16th century to the present and in which the term "sport". Results: materials obtained using the search engine "Google Books Ngram Viewer" indicate that, since the end of the 16th century in English-language prints, and therefore in social practice, for the generalized name of entertainment activities, people have been used, to some extent, as synonyms, the terms "sport" and "disport" (from the old French "disporter"). And in the process of historical development of society the frequency of using the term "sport", with respect to the frequency of using the term "disport", has constantly grown. Analysis of materials available in the library "Google Books" also indicates that in the process of socio-cultural evolution, the content of the concept of "sport" in English-speaking practice changed. Conclusion: analysis of the literature showed that the problem of the "beginning" of modern sports is one of the top priorities in the development of the general theory. The results of the study indicate that at the beginning of the 19th century the term "sport" was used in English-speaking practice for a more expressive definition of the subjective sense of people’s pleasure from completely different activities, that is, to emphasize that such activity was for them a kind of hobby , entertainment, fun.